The mysteries of the Ark of the Covenant - Römer, Thomas (Studia theologica, 2023)
The Ark of the Covenant, or Ark of Yhwh, has stimulated the imagination of many people from biblical times up to today: it has served as the inspiration for many stories, as the subject of paintings, and even the fodder for Hollywood directors, who still today show an interest in producing movies about the Lost Ark. There are probably many reasons for this fascination. For starters, the Hebrew Bible itself leaves many questions about the Ark open: What happened to the Ark after King Solomon brought it into the Temple? Was the Ark deported or destroyed when the Babylonians conquered Jerusalem? And what did the Ark originally contain?